MALE OR FEMALE, WHO IS THE HIGHEST? LIFE OPTIMISM IN CARDIOVASCULAR DISEASE PATIENTS - Putra, Rahman Pranovri; Ramadhanti, Auliya; Darmawan, Hakim (LPPM Universitas Jambi, 2023)
This study aims to analyze optimism in coronary heart patients and optimism in coronary heart patients based on gender differences as the novelty of this research compared to previous studies and it is the result of applied science in the field of public health. This type of research is survey research with a quantitative approach. The population in this study were 213 patients with coronary heart disease who had been clinically diagnosed by a doctor and were undergoing outpatient treatment at the Arifin Achmad Hospital in Pekanbaru. The number of samples in this study was 139 people. The data analysis technique used in this research is descriptive statistical analysis and inferential data analysis using the t-test. The results of the study show that there are differences in optimism in terms of gender in coronary heart patients. Therefore, these findings are useful for the development of positive psychology in the context of coronary heart patients.